Witchcraft, power and politics: exploring the occult in the South African Lowveld - Niehaus, Isak Arnold (Anthropology, culture, and society, 2001)
Introduction: exploring witchcraft, power and politics -- Society, cosmology and the making of witchcraft: continuity and change in the history of Green Valley, 1864-1995 -- Witches of the Lowveld and their familiars: conceptions of duality, power and desire -- Witchcraft and whites: further notes on the symbolic constitution of occult power -- Witches, cognates, affines and neighbours: the changing distribution of witchcraft accusations -- 'A witch has no horn': social tensions in the subjective reality of witchcraft -- Witch-hunting and political legitimacy: chiefs, comrades and the elimination of evil, 1930-1989 -- The ANC's dilemma: the symbolic politics of four witch-hunts in the 1990s -- Conclusion: witchcraft and the postcolonial state -- Appendix A. Fieldwork revisited -- Appendix B. Public perception map of South Africa -- Appendix C. The witchcraft suppression act no. 3 of 1957 -- Appendix D. Details of the alleged witches violently attacked, green valley, 1971-1985 -- Appendix E. Details pertaining to the victims of witch-hunts organised by the comrades, Green Valley, 1986-1989 -- Appendix F. Details of those accused of witchcraft, Green Valley, the Christmas witch-hunts, 1990 -- Appendix G. Details of those accused of witchcraft, new lines, Arthur's seat, October 1993 -- Appendix H. Details of those accused of witchcraft, Rooiboklaagte, November 1994 -- Appendix I. The Witchcraft Control Act as proposed by the commission of inquiry into witchcraft violence and ritual murders in the northern province of the Republic of South Africa